Atlas of Dermatologic Ultrasound - Wortsman, Ximena (Springer International Publishing, 2018)
This atlas presents a practical and systematic approach for performing dermatologic ultrasound. In recent years, the use of this imaging modality for diagnosing pathologic conditions of the skin, hair, nails, scalp, and soft tissues has grown dramatically and there is a demonstrated need for quick access to this information. For common dermatologic entities, richly-illustrated figures and drawings describe the ultrasound normal anatomy, technical guidelines, common findings, variants, key points, and tips and pitfalls. The extensive collection includes clinical and ultrasonographic correlations with 3D color Doppler ultrasound images and high-definition videos produced with state-of-the-art technology and relevant topics such as benign cutaneous and nail tumors and pseudotumors, skin cancer, vascular anomalies, facial ultrasound anatomy for cosmetic purposes, aesthetic complications, inflammatory diseases, etc. The Atlas of Dermatologic Ultrasound is a valuable resource and a must-have book for radiologists, dermatologists, plastic surgeons, sonographers, residents, and medical professionals who wish to strengthen their knowledge of the wide spectrum of sonographic presentations of dermatologic conditions and successfully integrate this field of ultrasound into their clinical practice. .